RHEED digital image analysis system for in-situ growth rate and alloy composition measurements of GaAs-based nanostructures - Sghaier, H.; Bouzaiene, L.; Sfaxi, L.; Maaref, H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Monitoring the intensity of the reflected spot in a RHEED image is the most important method used to control the growth of semiconductors in MBE. The accurate control of both layer thickness and alloy composition is particularly important for the growth of high quality heterostructures. Indeed, under such conditions, extremely uniform and high quality epitaxial devices become possible. RHEED intensity oscillation can be used as accurate, quick and direct measure of the growth rates and alloy compositions as well. Although analog signal could be obtained by using an optical fiber associated to a photo-detector PM tube and a plotter, this method is troublesome and limited. In some application, the availability of the intensity signal as a digital voltage is useful to realize further advanced analysis, and achieve feedback between growth dynamic and the external parameters, such as the cells temperatures and the synchronization of the shutters. In this paper we describe the advantages gained with the upgrade of our analog system into a digital package using CCD camera, frame grabber and a home made software. Its main purpose is to track RHEED intensity changes and measures the rate of oscillation. A state-of-the-art RHEED digital image analysis system gives us the necessary tools to gain insight into the thin film growth process and optimize material quality.